Analysis of suspended solids emissions from a combined sewage system using the Stormwater Management Model (SWMM) - Sakson, Grażyna (Geology, Geophysics and Environment, 2023)
The protection of water bodies requires the reduction of pollutant emissions from all major sources. In urbanized areas, these include: wastewater treatment plants (WWTPs) and (depending on the type of sewage system) combined sewer overflows (CSOs) and stormwater drainage outlets. WWTPs are usually monitored and emitted pollutant loads are known, but it is more difficult to assess the pollutant load discharged by CSOs and stormwater drainage systems. The article attempts to use the Stormwater Management Model (SWMM) to assess emissions of suspended solids from a large urban combined catchment. Suspended solids are the main pollutant of stormwater runoff in urban areas, and the dynamics of their emission from catchments is very diverse. The amount of suspended solids discharged by CSOs functioning in the given city was assessed in comparison with emissions from a wastewater treatment plant. The results show that CSOs discharge a pollutant load to the receiver which is comparable to WWTPs, but in a much shorter time and in a violent manner which can lead to the severe deterioration of receiving water quality. The modelling took into account the quality of dry weather sewage, the build-up of suspended solids, wash-off processes in the catchment area, and local precipitation characteristics. Factors affecting the quality of the obtained model and the accuracy of the emission level assessment were analysed.